Analysis of The Effect of Halal Labelization, Brand Image and Prices on Consumer Purchasing Decisions With Religious As Moderating Variables on Coastal Honey in Kertasada Village, Sumenep District - Idayana, Uni; Kurniawati, Dina (Nomico, 2024)
The need for honey in Indonesia alone reaches an average of 150,000 tons per year. This means that Indonesia has to import around 50% of its honey from abroad to meet this demand. This could also be an opportunity for local entrepreneurs to develop their honey business. Even though it seems traditional, the honey business opportunity has undergone modernization and development, from marketing to the processed honey itself. Coastal Honey is a honey bee cultivation business located in Kertasada Village. Coastal Honey, which has been established for around 8 years, is a business that has great prospects with profits increasing almost every year, coupled with the existence of resellers in various regions of Indonesia. The purpose of this research is to research and analyze the influence of halal labeling, Brand Image and Price on Consumer Purchasing Decisions with Religiosity as Moderating Variable on Coastal Honey in Kertasada Village, Sumenep Regency. This research is a quantitative exploration, with the population being the people of Sumenep, especially people who buy Coastal Honey. The testing strategy in this review uses purposive sampling testing, specifically determining samples with certain standards, especially consumers who buy Coastal Honey. Interviews and direct observations with the owner Coastal Honey and distributed questionnaires to 100 respondents which were used to collect data. As well as using data analysis techniques, namely Descriptive Statistics Test, Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Test, Coefficient of Determination Test and Hypothesis Test. The results of this research show that the Halal Labeling variable, Brand Image, Price and Religiosity have a significant effect on Purchasing Decisions partially and simultaneously. And the moderation results show that Religiosity moderates the relationship between Halal Labeling, Brand Image and Price on Purchase Decisions.